Retrieval of Gallbladder through Umbilical versus Epigastric Port-site during Laparoscopic Cholecystectomy: A 1-year Randomized Controlled Trial - Vishwanath M. Pattanshetti; Mihir Shankar; Shrishail C. Metgud (Journal of the Scientific Society)
Introduction: Postoperative pain remains one of the main causes of delay in resumption of activities after laparoscopic cholecystectomy (LC). The postoperative pain cause is multifactorial in nature. The port-site pain is one of the components. The study was undertaken to determine whether retrieval of the gallbladder (GB) through umbilical port is better than epigastric port in terms of lesser postoperative pain. Materials and Methods: A total of 80 patients were divided randomly into two groups of 40 each as Group A (GB retrieved through the epigastric port) and Group B (GB retrieved through the umbilical port). Demographics, clinical examination findings, other comorbid conditions, and duration of surgery were recorded. Postoperative pain after 1, 6, 12, and 24 h were evaluated. Statistical analysis was done using Fisher’s exact test and Chi-square test. Results: No significant difference was observed in demographic and clinical characteristics in either group (P > 0.05). The mean operative time was higher in Group A (73.55 ± 10.6 min) than in Group B (68.9 ± 10.3 min), but the difference was not statistically significant (P = 0.1676). The postoperative pain score in Group A was higher than that in Group B after 1 h (2.4 ± 0.5 vs. 0.95 ± 0.69; P < 0.0001), 6 h (2.95 ± 0.69 vs. 0.9 ± 0.55; P < 0.0001), 12 h (3.15 ± 0.67 vs. 1.15 ± 0.37; P < 0.0001), and after 24 h (3.65 ± 0.67 vs. 1.5 ± 0.61; P < 0.0001), the difference was statistically significant. Conclusion: In LC, the GB retrieval through the umbilical port could be a better alternative to GB retrieval through epigastric port in terms of lesser postoperative pain.